Legume Nodulating Bacterium, Achromobacter xylosoxidans Found in Tropical Shrub Agroecosystem, Sumatera, Indonesia - Sri Wedhastri; Dinar Mindrati Fardhani; Siti Kabirun; Jaka Widada; Donny Widianto; Rusdi Evizal; Irfan Dwidya Prijambada (Indonesian Journal of Biotechnology, 2013)
Legume nodulating bacteria (LNB), known also as rhizobia, are soil bacteria, which are able to form rootnodules and fi x nitrogen in the leguminous plants. The LNB availability in the soil depends on the type ofagroecosystem, where plant grows. In this study, we isolated LNB from the shrub agroecosystem in Sumatera,Indonesia, and obtained four selected bacterial strains. Among them, the isolate UGM48a formed root nodulein Macroptilium atropurpureum and showed highest number of nitrogenase activity. UGM48a also contains nifHand nodA genes. An analysis of the PCR-amplifi ed 16S rDNA and BLASTn analysis showed that UGM48adisplayed 96% similarity with Achromobacter xylosoxidans. In addition, UGM48a were successfully nodulatedGlycine max (L.) merr var. wilis. This is the fi rst report detecting A. xylosoxidans as nodule-forming species forGlycine max possesing the positive copy of nodA gene. Keywords : Legume Nodulating Bacteria, shrub agroecosystem, Achromobacter xylosoxidans, nodA, Glycine max